2006
DOI: 10.1007/s10750-006-0391-x
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton biomass in tropical reservoirs in southern Brazil

Abstract: In order to test the hypothesis that zooplankton biomass distribution (total and taxonomic groups) was influenced by the nutrient concentration and primary productivity distribution in three tropical reservoirs, subsurface samples were taken in the fluvial, transitional and lacustrine regions of three reservoirs (oligotrophic, mesotrophic and eutrophic) in southern Brazil (Paraná State) in March and September 2002. Zooplankton biomass ranged from 0.04 to 264.47 mg DW m -3 . Higher biomass values were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
(16 reference statements)
7
27
0
Order By: Relevance
“…Under the more eutrophic conditions of sites JA-01 and JA-02 during the dry season and JA-01 during the rainy season, the highest cladoceran biomasses were observed, a response similar to that reported by Bonecker et al (2007) and Serafim-Jú nior et al (2010) that observed an increase in Cladocera biomass and abundance at points with highest trophic state condition. This strong relationship between the Cladocera and the most eutrophic period and variables, like total phosphorus and chlorophyll a, is evidenced by the CCA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Under the more eutrophic conditions of sites JA-01 and JA-02 during the dry season and JA-01 during the rainy season, the highest cladoceran biomasses were observed, a response similar to that reported by Bonecker et al (2007) and Serafim-Jú nior et al (2010) that observed an increase in Cladocera biomass and abundance at points with highest trophic state condition. This strong relationship between the Cladocera and the most eutrophic period and variables, like total phosphorus and chlorophyll a, is evidenced by the CCA.…”
Section: Discussionsupporting
confidence: 86%
“…This close relationship between the values of biomass and TSI was also observed by Bonecker et al (2007) in three reservoirs in Paraná State.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Generally, few species are dominant in high densities in eutrophic reservoirs (Sendacz & Kubo, 1982;, feeding mainly on Cyanobacteria blooms and associated bacteria-according to Maitland's (1978) affirmative. In oligotrophic and also in mesotrophic reservoirs studies indicated higher richness and lower abundances (Nogueira, 2001;Bonecker et al, 2007). However, observed higher species richness in an eutrophic reservoir, as well as Velho et al (2005); Perbiche-Neves et al (2007) and Bini et al (2008) in another eutrophic reservoir.…”
Section: Introductionmentioning
confidence: 79%
“…For example, Nogueira (2001) and Sampaio et al (2002) have found high frequency of Collotheca sp., Conochilus coenobasis, C. unicornis, Keratella americana, K. cochlearis and Polyarthra vulgaris in oligotrophic reservoirs of Paranapanema River, in contrast with Matsumura- , who observed abundance peaks of C. coenobasis and K. americana in an eutrophic reservoir. Another example is the study of Bonecker et al (2007), that studied 30 reservoirs in Paraná State (Brazil), and concluded that Hexartra intermedia, Synchaeta pectinata and Trichocerca insignis indicated eutrophic conditions and Trichocerca pusilla and T. similis mesotrophic conditions. Thus, only the high richness of Brachionidae can be pointed out as indicator of eutrophic conditions, even considering the other relationships commonly found in the literature.…”
Section: Discussionmentioning
confidence: 99%